Effect of Durian Fruit on Blood Pressure - Brigitta Olivia Sinulingga; Angwen Rial Huga; Laurencia Alimin (GLOBAL HEALTH SCIENCE GROUP, 2020)
Durian or Durio zibethinus is a tropical fruit originating from Southeast Asia. Durian is often known as